Impact assessment of Controlled Mechanical Ventilation systems for air quality in school buildings: a study protocol - Maria Francesca Rossi; Flavia Beccia; Raimondo Leone; Clara Peretti; Luca Verdi; Costanzo Di Perna; Sergio Montelpare; Giuseppina Caggiano; Umberto Moscato; necessARIA Working Group (Epidemiology, Biostatistics and Public Health)
Background: Indoor air is an important public health issue and the COVID-19 pandemic has highlighted even more the importance of indoor air quality in schools. One of the main measures to preserve good indoor air quality is to maintain adequate indoor air exchange, and energy-efficient mechanical ventilation has been shown to be effective in improving indoor air quality and health of the occupants.